Melaka Moving Forward To Incineration Technology Management to Overcome Municipal Solid Waste (MSW) Problem - F. Fam, S; Utami, S; D. Prastyo, D; L. Maukar, A; A.A.M. Khairuddin, M; H. Mustaffa, M (International Journal of Engineering and Technology, 2018)
Exponential population growth in cities have generated huge amounts of municipal solid waste (MSW). This includes Melaka which in addition has experienced a rising number of tourists over recent years. The two factors combined have brought to the production of approximately 1200 tonnes of waste per day. Landfilling is the general method of disposal but has brought with it challenges of insufficient territory. To address the issue, this study suggests the use of incineration technology as an alternative method. Expertsâ€™ opinions are generated regarding the suitability of implementing the technology in Melaka. A qualitative method is used by interviewing top management of the secretariat of Melaka Green Technology Council and Melaka Green Technology Corporation. PESTLE analysis approach is incorporated as an explorative research tool. The findings showed that Melaka has the capabilities of implementing the incineration technology on a large scale.Â Â